PSIV-11 The effect of a high sugar supplement versus a beef supplement during pregnancy on offspring hepatic gene expression in a swine biomedical model. (5th December 2019) - Hall, Jerica R; Hoyle, Ashley; Hirchert, Mara; Swanson, Kendall C; Vonnahme, Kimberly A; Ward, Alison
Abstract: Our objective was to investigate the effect of a maternal supplemental calorie source, (high protein or high sugar) on offspring developmental programming of metabolic gene expression. Multiparous sows (n = 35) were bred to one of two full-sibling boars. Sows were fed a corn and soybean meal-based diet and randomly assigned to one of four isocaloric supplement treatments: 126 g of the basal diet, (CON, n = 5); 85 g of crystalized sugar (SUGAR, n = 5); 110 g of cooked ground beef (BEEF, n = 6); or a combination of 55 g cooked beef and 43 g of crystalized sugar (B+S, n = 5). Supplements were fed three times daily from d 40 of gestation through d 18 of weaning. A male and female offspring of median weight from each sow were individually housed and phase fed standard production diets. Offspring were harvested at d 160 of age and a liver tissue sample collected. Expression of the following genes was quantified via qPCR with hypoxanthine phosphoribosyltransferase 1 (HPRT1) as the reference gene: pyruvate carboxylase (PC); phosphoenolpyruvate carboxykinase 1 (PCK1); lipase C hepatic type (LIPC); fibroblast growth factor 21 (FGF21); glucose-6 phosphatase catalytic subunit (G6PC); and fructose 1, 6-biphosphate (FBFase). Genes were selected based on their function in hepatic metabolism. Data were analyzed using the GLM procedure of SAS with sex, treatment, and interaction as fixed effects. Sex influenced (P < 0.05) expression of PC and FBFase, with males having greater expression than females (1.38 vs. 0.63 ± 0.14 and 1.15 vs. 0.82 ± 0.09, respectively). However, there was no effect of treatment or sex by treatment interaction on hepatic expression of the genes studied (P > 0.05). Therefore, we conclude that supplemental caloric source during pregnancy does not alter developmental programming of the stated liver metabolic genes in peripubertal offspring.